Īḻattut Tamiḻ ilakkiya vaḷarcci : 14ām nūṟṟāṇṭu mutal 18ām nūṟṟāṇṭiṟutivarai - Naṭarācā, Ka. Ce (Koḻumput Tamiḻc Caṅka Veḷiyīṭu, 1982)
Study of the development of Tamil literary forms and traditions in Sri Lanka, 14th to 18th cent.